Gambaran Pola Makan dan Kesehatan Mahasiswa UIN Sumatera Utara Program Studi Sistem Informasi - Dilla Natasya; Ahmad Fikri Saragih; Farhan Suradinata; Sendy Ivanka Kurniawan; Ferry Isnawan; Adelyna Oktavia Nasution (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Students in the Information Systems Program at UIN Sumatera Utara tend to have irregular eating patterns with high consumption of fast food. This habit contributes to various health problems such as digestive disorders and decreased concentration. This study was conducted to investigate the eating patterns of students in the Information Systems Program at UIN Sumatera Utara and their relationship with their health conditions. Through a quantitative survey of 50 respondents, the results showed that most students eat less than three times a day, with the highest frequency being twice a day (48%). Additionally, the majority of students consume fast food 1–2 times a week (60%). Analysis using the Chi-Square test revealed a significant association between the frequency of fast food consumption and students' health conditions (p < 0.05). Many students experienced health issues such as stomach problems and fatigue related to their unhealthy eating patterns. These findings emphasize the need for nutrition education and the implementation of practical healthy eating patterns to support students' health and academic performance.